Mr. Wolf's pancakes - Fearnley, Jan. (London : Egmont, 2008)
Mr. Wolf asks some of his neighbors to help him make pancakes, but they all refuse; however, when the pancakes are done, they expect to share in the feast. Includes read-along CD.
Compact disc.
3.4
K-3
Keywords: Pancakes, waffles, etc. -- Juvenile fiction; Wolves -- Juvenile fiction; Characters in literature -- Fiction; Pancakes, waffles, etc. -- Fiction; Wolves -- Fiction; Characters and characteristics in literature -- Fiction; Compact discs; Pancakes, waffles, etc. -- Fiction; Wolves -- Fiction; Compact discs